More than a feeling: Analyzing community cognitive and affective perceptions of the Block Island offshore wind project. (June 2022) - Russell, Aaron; Firestone, Jeremy
Abstract: In this article, we study local perceptions of the Block Island Offshore Wind Project (United States) by evaluating both cognitive (rational) and affective (emotional) responses with the goal of learning about how each relates to project support and opposition and how a nearby island population differs from that of the coastal residents farther away. Multivariate regression is used and relies on a dual-process model of evaluation. Both the island and coastal populations break down similarly in terms of the strength of cognitive and affective influencers, with an affective model explaining more variance than a cognitive one. A combined model performed the strongest and emotions still tend to dominate. Community engagers, both developers and regulators, must address renewable energy transitions in culturally and environmentally sensitive places through incorporation of affective perception components and other holistic approaches.